ТHE STRUCTURAL USES OF THE DEFINITE AND INDEFINITE ARTICLES IN MODERN ARMENIAN AND MODERN STANDARD ARABIC (Journal of Oriental Studies, 2024)
Stemming from two different linguistic family trees (the Indo-European family and the Semitic language group respectively) the Armenian and Arabic languages comprise of entirely different linguistic systems. Subsequently in learning and teaching processes differences are typically emphasized, and similarities are often overlooked. The purpose of this compare-and-contrast article is to outline the structural uses of the definite and indefinite articles in Modern Armenian and Modern Standard Arabic in the context of cross-linguistic typology. While laying out the main rules and generalizations, this article discusses the structural similarities and differences of the two languages through a qualitative approach. The overall purpose of the article is to demonstrate the many commonalities between the usage of definite/ indefinite article in two languages. The aim of such methodology is to provide an analytical baseline relating the learned language to the learner’s native tongue. The usage of such a baseline in educating process will lead to more efficient comprehension and natural acquisition of the language.
Keywords: Definite Article; Indefinite Article; Zero Article; Article Placement (grammar); Arabic; Armenian; Grammatical Category of Definiteness; Cross-linguistic Typology; Means of Grammatical Expression